2018
DOI: 10.1590/0047-2085000000191
|View full text |Cite
|
Sign up to set email alerts
|

Sonolência diurna excessiva e qualidade de vida relacionada à saúde dos professores universitários

Abstract: RESUMO Introdução Problemas relacionados ao sono interferem na qualidade de vida das pessoas. Este trabalho tem o objetivo específico de analisar a influência da sonolência diurna excessiva na qualidade de vida dos docentes. Métodos Para tal pesquisa, aplicaram-se três questionários. Para avaliar a qualidade de vida, usou-se o questionário Medical Outcomes Study 36 – Item Short – Form Health Survery. O sono foi avaliado pela escala de Epworth e as demais variáveis foram avaliadas por um questionário semiestrut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
3
12
0
16
Order By: Relevance
“…In a survey of 107 professors from a federal university, it was observed predominance of those with a doctorate degree (68.2%) (15) . The same was verified in a survey of 270 professors from the Federal University of Rio Grande, in which 75% had a doctorate degree (14) . The predominance of professors with doctoral degrees in the studies found is due to the requirement of this degree in federal and state public institutions for investiture in the position of assistant professor.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In a survey of 107 professors from a federal university, it was observed predominance of those with a doctorate degree (68.2%) (15) . The same was verified in a survey of 270 professors from the Federal University of Rio Grande, in which 75% had a doctorate degree (14) . The predominance of professors with doctoral degrees in the studies found is due to the requirement of this degree in federal and state public institutions for investiture in the position of assistant professor.…”
Section: Discussionmentioning
confidence: 67%
“…There was a predominance of male professors, married, without children, who live with the family and presented a mean age of 38.80 years old, considered young adults. In a cross-sectional study that analyzed the influence of excessive daytime sleepiness on the quality of life of 270 university professors (including those in the health area), female (52.2%) predominated in the 30 to 39 age group (35.5%) and married (65.0%) (14) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O sono define-se através de duas componentes: duração (quantidade de sono por noite) e qualidade do sono, isto é, a satisfação percebida do sono pelo indivíduo (e.g., Campsen & Buboltz, 2017). A qualidade do sono revela-se essencial para o desenvolvimento do ser humano (Lopes, Milheiro, & Maia, 2013;Yan et al, 2018), uma vez que o sono exerce um papel homeostático fundamental na redução do stress físico e melhora a qualidade de vida dos indivíduos (Amaro & Dumith, 2018). A qualidade do sono pode ser influenciada pelo tipo de trabalho e a dedicação horária ao mesmo, tal como acontece com o tipo de atividade que os estudantes universitários precisam de despender diariamente (Benavente, Silva, Higashi, Guido, & Costa, 2014), estando estes sujeitos a horários irregulares de aulas e provas académicas que podem afetar o padrão do ciclo de sono-vigília (Carvalho et al, 2013).…”
Section: Introductionunclassified